Pengaruh Good Corporate Governance terhadap Risiko Kredit dengan Profitabilitas sebagai Variabel Moderasi : Studi Empiris pada Perusahaan Perbankan yang Terdaftar di BEI Periode 2022-2024 - Athifa Aswa Ramadhani; Alexa Joy Valerie; Carmelita Endera; Aminah Imro’atus Sholiha; Asyifa Putry Fadhilla; Dias Permata Ukir Purbo Nata; Rohmawati Kusumaningtias; Ambar Kusumaningsih (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
Credit risk remains one of the main challenges faced by the banking industry, particularly in maintaining financial stability and public trust. Weak corporate governance may increase the potential for non-performing loans, while profitability can influence the effectiveness of risk management practices. This study aims to examine the effect of Good Corporate Governance (GCG) on credit risk and to analyze the moderating role of profitability in banking companies listed on the Indonesia Stock Exchange during 2022–2024. The research applied a quantitative approach using Moderated Regression Analysis (MRA). The sample consisted of 46 banking firms selected through purposive sampling, resulting in 108 observations. Credit risk was measured using the Non-Performing Loan (NPL) ratio, GCG was proxied by the proportion of independent commissioners, and profitability was measured by Return on Assets (ROA). The findings indicate that GCG has a negative and significant effect on credit risk, suggesting that stronger governance practices contribute to lower levels of non-performing loans. Profitability does not directly affect credit risk; however, it strengthens the relationship between GCG and credit risk reduction. These results highlight the importance of effective governance supported by stable profitability in improving bank risk management performance.